The limits of law in the face of individual's moral autonomy: the risks of the ethical maximum (Revista do Tribunal Regional Federal da 3ª Região, 2013)
In an intellectual and legal environment in which neoconstitutionalism predominates, proposing a rapprochement between law and morality, it seems important to emphasize that, in addition to incorporating moral precepts, law has also evolved to exclude certain moral contents and fields from its scope. In this article, we will discuss the relationship between law and morality in the philosophy of law (1), and then outline concepts and principles that limit the law in the face of the individual's moral sphere (2), analyzing Supreme Court decisions that have dealt with the issue (3) and presenting conclusions (4).
Keywords: moral autonomy; limits of law; freedon of religion; laicity; freedom